2014
DOI: 10.2460/javma.244.8.940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of epidural analgesia with opioids on the prevalence of urinary retention in dogs undergoing surgery for cranial cruciate ligament rupture

Abstract: Administration of preservative-free morphine into the epidural space was not associated with clinically important urinary retention in dogs undergoing elective orthopedic procedures. Systemic administration of opioids may be associated with urinary retention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 13 publications
2
12
0
Order By: Relevance
“…We did not find any difference between the two groups in the time from extubation to the first spontaneous urination. These results are in line with findings reported in the current literature, both in human and in canine anesthesia, providing evidence that postoperative urine retention is more likely related to the type and the dose of opioid used systemically and the concomitant administration of other drugs …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We did not find any difference between the two groups in the time from extubation to the first spontaneous urination. These results are in line with findings reported in the current literature, both in human and in canine anesthesia, providing evidence that postoperative urine retention is more likely related to the type and the dose of opioid used systemically and the concomitant administration of other drugs …”
Section: Discussionsupporting
confidence: 92%
“…Seventy‐five percent of dogs in the EPID group urinated within 6 hours after surgery, which is in line with earlier findings . High doses of systemically administered full μ‐opioid agonists are known to decrease micturition, probably through their spinal effects and by causing the release of antidiuretic hormone in anesthetized patients . We did not find any difference between the two groups in the time from extubation to the first spontaneous urination.…”
Section: Discussionsupporting
confidence: 91%
“…Information in the published literature does not always support the link between urinary retention and epidural morphine administration. Recent publications report no evidence of epidural morphine administration being a direct cause of urinary retention in the dog (Kalchofner Guerrero et al 2014;Peterson et al 2014), whereas older studies suggested an association (Rawal et al 1983;Herperger 1998). This raises the question of whether failure to void urine after anesthesia and surgery may be associated with epidural opioid administration, the result of increased production of antidiuretic hormone as part of the endocrine response to anesthesia and surgery (Hauptman et al 2000), fluid retention (Boscan et al 2010) or simply the result of an inability to posture to urinate.…”
Section: Figurementioning
confidence: 99%
“…Myoclonic activity upon recovery from anesthesia was also reported following intrathecal administration of morphine in dogs (15, 100) but this is not a clinical issue with epidural injections, providing that the maximum dose of 0.1 mg kg −1 is respected and accidental puncture of the subarachnoid space does not take place during needle insertion (103). Studies showed that approximately 3% of dogs receiving epidural morphine showed urinary retention postoperatively (6, 104). The prevalence of urinary retention increases when morphine is administered epidurally for postoperative pain control via indwelling epidural catheter.…”
Section: Opioidsmentioning
confidence: 99%